Potis Calculia: Learning Resources Platform for Dyscalculia - Vinothini, Vinothini; Mustapha, Aida; Jae Won, Yun; Mandhana, Akansha (International Journal of Engineering and Technology, 2019)
Dyscalculia is severe difï¬culty in making arithmetical calculations. The population of dyscalculia children are comparably lower than otherDisabilities such as the down syndrome, hence the resources for are highly insufï¬cient. However, since the population is elevating slowly, the gap in learning resources has to be addressed. This research proposes an integrated learning platform using website that offers learning materials speciï¬c for dyscalculia children. The development methodology takes into account understanding the brain process in effort to help the children to overcome their disabilities. Evaluation results showed positive feedback among the users and will be continuously improved to ensure they have equal opportunities in learning.Â Â